Raising awareness about recycling in Ukraine based on the principles of the EU circular economy - Kreish, Alina; Yastremska, Larysa; Korniienko, Iryna; Garkava, Kateryna; Kosoholova, Liudmyla; Huliaiev, Vitalii; Anatskyi, Andrii (Problems of Environmental Biotechnology, 2024)
The article considers the dissemination of information awareness on recycling in Ukraine based on the principles of the EU circular economy